Circulating nucleic acids in plasma and serum proceedings of the 6th international conference on circulating nucleic acids in plasma and serum held on 9-11 November 2009 in Hong Kong - Gahan, Peter B. (Springer eBooks., 2011)
DNA and RNA fractions have been isolated from a variety of sources including: whole blood, serum, plasma, the surface of blood cells, urine, saliva and spinal fluid from both healthy individuals and patients. The ability to isolate, quantify, and analyze these molecules has led to the identification of specific nucleic acid fragments related to a variety of clinical disorders thereby permitting their early diagnosis and prognosis. This volume encompasses the proceedings of the 6th international conference on circulating nucleic acids in plasma and serum held from the 9th to the 11th of November 2009 in Hong Kong. The topics that are covered in these proceedings include: - Nucleic Acids in Oncology - Nucleic Acids in Foetal Medicine - The Biology of CNAPS - New Technologies for CNAPS - Other Clinical Exploitation of CNAPS